2017
DOI: 10.18869/acadpub.nfsr.4.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effects of Montmorillonite and Glycerol on the Properties of Polyvinyl Alcohol-montmorillonite Films

Abstract: A B S T R A C TBackground and Objectives: Preparation and evaluation of nanocomposite films have become prevalent in recent years. Depending on the purpose of using the film, and considering the effects and interaction effects of nanomaterial and other modifiers on the film properties, the amounts of nanomaterials and modifiers should be optimized. The effects of montmorillonite (MMT), glycerol (GL), and their interaction effects on the properties of polyvinyl alcohol-montmorillonite (PVA-MMT) films were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The interactions of Gly with CS, MMT, and SSA led to a decrease in total peak intensity, specifically in the fingerprint area, indicating the plasticizing function of Gly. 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions of Gly with CS, MMT, and SSA led to a decrease in total peak intensity, specifically in the fingerprint area, indicating the plasticizing function of Gly. 43 …”
Section: Resultsmentioning
confidence: 99%
“…The interactions of Gly with CS, MMT, and SSA led to a decrease in total peak intensity, specically in the ngerprint area, indicating the plasticizing function of Gly. 43 SEM & AFM analysis of the membranes SEM pictures were taken to examine the morphology of the prepared membranes. Before the analysis, the membranes were coated with platinum.…”
Section: Ftir Analysis Of the Membranesmentioning
confidence: 99%
“…It was reported that 30 min sonication time caused more dispersion of nanomaterial in polymer; as a result, properties of the films increased. [ 47,48 ] Ultimate tensile strength, elongation at break (%), and Young's modulus of antibacterial PVA & CNF (treated/untreated) films reinforced at 20, 30, 40, and 50 wt% blended with PEG, CHT are determined from stress–strain curves and presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The GL promoted a widening of the -OH band between 3000 and 3500 cm -1 , which pointed out the different nature of the -OH groups in these polyelectrolytes. The interactions of GL within the CS, PVA and SSA resulted in a reduction of the overall peak intensity, especially in the fingerprint region, which proved the plasticising effect of GL [30].…”
Section: Physico-chemical Characterisation Of the Membranes: Macrosco...mentioning
confidence: 91%